Technique for Optimizing Morganian Cataract Phacoemulsification - O. L. Fabrikantov; E. S. Pirogova; S. I. Nikolashin (Oftalʹmologiâ, 2018)
Purpose: to optimize the technique of hypermature Morganian cataract phacoemulsification.Patients and methods. 18 patients (18 eyes) with hypermature Morganian cataract were examined. Group I included 8 patients who underwent surgical intervention according to the improved technology using the iridocapsular retractors. Group II included the retrospective results of phacoemulsification with IOL implantation performed according to a standard technique in 10 patients. The optimizing surgical technique in patients of group I consisted in the consecutive usage of four iridocapsular retractors: when creating a capsulorhexis — to stabilize the capsular bag during the circular rupture of the anterior capsule; during the nucleus phacoemulsification — to stabilize the complex: capsular bag, nucleus, capsular ring — in the sagittal plane and additional (together with the capsular ring) support of the capsular bag fornices.Results. No complications were noted in patients of group I. In patients of group II there were two ruptures of the posterior capsule (20%), two cases of re-implantation of a capsular ring because of the stop of its edge into the fold of the capsular bag fornix, one rupture of the anterior capsulorhexis border without its transition to the posterior capsule. In group I there were no any complications in the postoperative period. In group II we noted two corneal oedemata, Descemet membrane folds, which were jugulated by the conservative treatment on the 4–5th days postoperatively.Conclusion. The optimizing technique of hypermature Morganian cataract phacoemulsification with the use of four iridocapsular retractors and capsular ring allowed reducing the number of intraoperative complications in comparison with the standard technique and making the surgical intervention more effective and safe.